The Successful Digital Transformation of Human Resource Management: A Study of Regional Water Supply Enterprises (BUMD Air Minum) in West Kalimantan - Wijaya, Yohannes Andriyus; Afifah, Nur; Mustaruddin, Mustaruddin; Rosnani, Titik (Jurnal Ragam Pengabdian, 2026)
Digital transformation in human resource management (HRM) has become an urgent necessity for public sector organizations, including Regional Water Supply Enterprises (BUMD Air Minum) in West Kalimantan. This study is a pilot study aimed at testing and exploring the directional relationships among variables as a foundation for a full-scale study. Variables examined include transformational leadership, organizational culture, employee digital competency, IT infrastructure, and top management support as independent variables, with HRM digital transformation success as the dependent variable. A quantitative approach with simple random sampling was employed involving 30 respondents from Regional Water Supply Enterprises (BUMD Air Minum) in West Kalimantan, randomly selected. Results were analyzed using regression analysis with SPSS version 26, showing that transformational leadership, employee digital competency, and top management support have positive and significant effects, while organizational culture and IT infrastructure show positive but non-significant trends at this sample size. This pilot study confirms instrument readiness for a full-scale study across all BUMD Air Minum in West Kalimantan.